SUB-NATIONAL PUBLIC FINANCE AND ECONOMIC DECENTRALIZATION: CHALLENGES OF THE PENDING AGENDA FOR ECONOMIC DEVELOPMENT - Gonzalez Taranco, Carlos (2022)
This article is based on the economic concentration analysis, and its aim is to analyze the fiscal decentralization, production concentration, demographic density, districts typology, to state guidelines to economic development considering international experiences to promote public policies discussions oriented to productive decentralization, whose objectives were oriented to integration, equity and competitiveness of our country.